The constraints and challenges faced by the Malaysian SMES / Masmawarni Sohhimi - Sohhimi, Masmawarni (Faculty of Business and Management, 2011)
Small and medium enterprises (SMEs) are playing a significant role in the economy stability and growth of a country. SMEs are considered as the backbone of economic growth in all countries because they account for 80 percent of global economic growth. SMEs also contribute a large share of the manufactured exports of the East Asia such as Taiwan, China, India and the Republic of Korea. In Malaysia, it is apparent that SMEs play a vital role in the economic development of the country. In spite of that, in developing this country, there are a lot of challenges faced by the Malaysian SMEs that may hinder their business operation. There were a lot of studies that had been conducted by other researchers like Peter Mousley (2007), Dr. Chin Yee Whah (2003), Burns (2001), and Saleh (2006). These researchers had revealed many challenges faced by the owners of the SMEs plus its effects to the companies. In order to recognize more challenges, this research paper is was conducted and the result of this study might be useful not only to the owners of SMEs, but also other parties such as the government and financial institutions.